Training of scholarly article writing using quantitative methods for teacher competency development - Lustina Fajar Prastiwi; Hadi Sumarsono; Imam Mukhlis; Annisya' Annisya' (University of Merdeka Malang, 2022)
Teaching competency development can be improved by increasing research and scholarly writing. The benefits of research can increase knowledge and insight, improve the quality of learning in the classroom and increase collaboration through a collaborative research system. However, teachers are still unable to write scientific articles due to the lack of knowledge about research methods and analysis tools that affect the lack of scientific writing. This community service program aims to provide knowledge and improve the ability of economics teachers in the field of research, especially quantitative analysis in the use of analytical tools related to the learning process and research preparation by Blitar Regency/City Economics MGMP teachers. The activities carried out were socialization, training on quantitative methods, and the use of statistical analysis tools. The results are an increase in the number of scientific articles written by teachers, an increase in knowledge about research methods and the use of SPSS, and an increase in the number of scientific articles published by teachers. In addition, the participation satisfaction survey shows that the community service team has carried out activities according to the needs of teachers and has had significant results in accordance with the goals of community service.